Micro-Credit in Conventional Banking: Would Islamic Banking be the Golden Age for Entrepreneurs? -The Mauritius Case Study - Rajendra Parsad GUNPUTH (Journal of Social and Development Sciences, 2014)
The broad aim of this paper is to make an analogy between conventional banks and Islamic banking in micro-credit and the incentives they may provide for entrepreneurs and small and medium enterprises (SMEs) in a Mauritian perspective? Indeed, in Mauritius traditional or conventional banks are more and more reluctant to give loans to entrepreneurs who are considered as high risk investors (their fragile entrepreneurs may collapse unexpectedly) despite they create jobs and employment. In contrast, in most Islamic countries Islamic banks allow businessmen and investors among others to have loans without interest (or riba) according to sha’ria compliants and tailor made Islamic contracts (mudabara and musarakha) to support their innovations and proposals. Despite Islamic banking is at its burgeoning state it has expanded considerably in most Islamic and Arab countries. Would Islamic banks uproot conventional banks irrespective it is in Islamic countries or Western countries? This paper therefore adds to an already abundant literature on the subject-matter but it enlightens a central issue: would Islamic banking, sha’ria law and Islamic economies be the golden age for entrepreneurs and SMEs in Mauritius and worldwide?